Conservative Treatment of Lung Perforation Secondary to Retained Catheter in an Extremely Low-Birth-Weight Premature Infant - Arda, Mehmet Surhan; Hamrick, Miller C.; Kane, Timothy D. (European Journal of Pediatric Surgery Reports, 2015)
Airway injury may occur during the use of any instrumentation in premature infants. A surgical approach for the treatment of lung perforation in extremely low-birth-weight infants has been recommended in the past. Here, we present a case of lung perforation in an ex–28-week, 730-g premature infant, who sustained lung perforation, secondary to an 8-Fr suction catheter used to administer surfactant, in which the broken catheter was retained in the airway. Following removal of catheter by endoscopy, tension pneumothorax had occurred. Attempts were made to treat the patient with single chest tube, unfortunately as it was not efficacious, the second one was placed on the ipsilateral side of hemithorax and the patient recovered without further surgery.
Keywords: lung perforation; tension pneumothorax; treatment; premature